Cycling a Tether into Multiple Rings: Pt‐Bridged Macrocycles for Differentiated Guest Recognition, Pseudorotaxane Transformations, and Guest Capture and Release. Issue 4 (14th December 2022) - Soto, Miguel A.; Carta, Veronica; Suzana, Ingrid; Patrick, Brian O.; Lelj, Francesco; MacLachlan, Mark J.
Abstract: Macrocycle engineering is a key topic in supramolecular chemistry. When synthesizing a ring, one can obtain either complex mixtures of macrocycles of different sizes or a single ring if a template is utilized. Here, we unite these approaches along with post‐synthetic modifications to transform a single tether into multiple rings—up to five per tether. The macrocycles contain two bridged phenylpyridine ligands that are connected through a Pt atom, which defines the rings' shape, size, and host activity. All rings undergo redox reactions (between Pt II and Pt IV ) that allow for large conformational changes. Their reactivity, together with their host performance, is a convenient way to control the capture and release of guests, to mediate ring transformations, and to control pseudorotaxane‐to‐pseudorotaxane conversions. This novel approach could serve to assemble other libraries of small ring molecules, create cyclic polymers bridged by responsive‐at‐metal nodes, and produce processable mechanically interlocked molecules. Abstract : Wrapping a tether around a platinum ion gives five different pseudocrown ethers that differ in shape and host activity. The Pt ion in the rings is redox‐active and stays that way even if the host is occupied by a guest, facilitating expeditious pseudorotaxane‐to‐pseudorotaxane transformations, guest‐directed ring reactivity, and release of guests upon redox stimulation.